Pengamalan Pancasila Sebagai Pembentukan Nation Character di Era Revolusi Industri 4.0 - Yayu Nur Faidah; Dinnie Anggraeni Dewi (ASANKA: Journal of Social Science And Education, 2021)
This study aims to re-apply the values contained in Pancasila as the formation of the nation's character in the era of the industrial revolution 4.0. The problem of this research is motivated by a visible attitude about the appreciation of Pancasila values which is starting to disappear. This study uses a literature study method, where data collection techniques are carried out by conducting a review of books, literature, notes, journals that are related to the problems discussed. The results of the study concluded that in the era of the Industrial Revolution 4.0, Indonesia will experience major changes in all aspects of life. Especially technology. Everything that is done will be related to modern technology, the internet, and the advancement of human thought. The more sophisticated the technology, the more the character of the nation will fade in today's young generation which has an impact on the social and cultural environment of the nation. It is possible that the young generation in the future will have a free, apathetic and individualistic character. So the efforts that can be made to prepare the younger generation from now on to apply Pancasila values in daily life to change the nation's character for the better with a clear, directed, and structured goal are also very relevant to be applied in Indonesia. The values contained in Pancasila will be able to build the nation's character in the younger generation and be able to fortify the younger generation from habits that are not in accordance with the values of Pancasila.